2018
DOI: 10.29252/ijrm.16.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Serum heat shock protein 70 in preeclampsia and normal pregnancy: A systematic review and meta-analysis

Abstract: Background:Preeclampsia, a severe complication of human pregnancy is one of the main causes of maternal, fetal, and neonatal morbidity and mortality with unclear pathogenesis. Heat shock protein 70 (HSP70) is one of the factors that can mediate cytoprotective, antiapoptotic, and immune regulatory effects.Objective:This meta-analysis was performed with aim to evaluate HSP70 in preeclampsia and normal pregnancy.Materials and Methods:The original publications reporting the serum HSP70 levels in preeclampsia and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…Hsp70 is associated with endothelial activation in placental vascular disease (25) and serum levels are increased in cases of preeclampsia (24,47,48). Hsp70 levels are furthermore significantly elevated in patients exhibiting hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome) compared to patients with severe preeclampsia without HELLP syndrome (24,49).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 is associated with endothelial activation in placental vascular disease (25) and serum levels are increased in cases of preeclampsia (24,47,48). Hsp70 levels are furthermore significantly elevated in patients exhibiting hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome) compared to patients with severe preeclampsia without HELLP syndrome (24,49).…”
Section: Discussionmentioning
confidence: 99%
“…PE is a common systemic obstetric disorder whose specific pathogenesis has not yet been fully explained. However, it is becoming increasingly accepted that oxidative stress, and maternal systemic inflammatory response have a key role in the pathogenesis of PE [8,15,16], which may induce the expression of HSP70 [18].…”
Section: Discussionmentioning
confidence: 99%
“…As a stress protein, HSP70 plays a pivotal role in protecting cells against apoptosis, oxidative damage and genetic damage [17]. Placental ischemia, oxidative stress and maternal systemic inflammatory response, which play important roles in the pathogenesis of PE, have been shown to induce the expression of HSP70 [18]. Moreover, studies indicated that HSP70 is involved in the pathogenesis of hypertension and associated diseases such as coronary heart disease, atherosclerosis, ischaemic stroke, Parkinson's disease, high-altitude illness and the forth, and there were high levels of HSP70 in serum, plasma and placental tissue of PE patients [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies had found that serum HSP70 in PE patients was significantly higher, but Livingston et al [found that the serum HSP70 in patients with severe PE was not higher than that in normal pregnant women [42][43][44]. Based on this disagreement, Saghafi et al conducted a meta-analysis and found that the serum HSP70 in patients with PE was significantly higher than that in normal pregnant women, although only seven studies were included [45]. Moreover, Hromadnikova et al found that the mRNA level of HSP70 in patients with PE is high, but it has nothing to do with the severity of the disease [46] .…”
Section: Heat Shock Proteinmentioning
confidence: 99%